2004
DOI: 10.1177/0095399703258735
|View full text |Cite
|
Sign up to set email alerts
|

Prospective Evaluation of Thermal Capsulorrhaphy for Shoulder Instability

Abstract: The high rate of unsatisfactory overall results (37%), documented with longer follow-up, is of great concern. The authors conclude that enthusiasm for thermal capsulorrhaphy should be tempered until further studies document its efficacy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
96
0
2

Year Published

2007
2007
2015
2015

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 129 publications
(100 citation statements)
references
References 51 publications
2
96
0
2
Order By: Relevance
“…Additional evidence of the effect of prior surgery having an effect on revision rates is supported by the level 2 cohort study of 100 athletic shoulders by Bradley et al [8] in which they reported 25% (2 of 8) of their revisions had undergone a prior thermal capsulorrhaphy procedure. Thus, prior surgery resulting in poor quality capsular, especially as a result of thermal shrinkage of capsular tissue may weaken the capsulolabral complex, resulting in unsatisfactory patient outcomes leading to further revision and failure [16] .…”
Section: Concomitant Injuriesmentioning
confidence: 99%
“…Additional evidence of the effect of prior surgery having an effect on revision rates is supported by the level 2 cohort study of 100 athletic shoulders by Bradley et al [8] in which they reported 25% (2 of 8) of their revisions had undergone a prior thermal capsulorrhaphy procedure. Thus, prior surgery resulting in poor quality capsular, especially as a result of thermal shrinkage of capsular tissue may weaken the capsulolabral complex, resulting in unsatisfactory patient outcomes leading to further revision and failure [16] .…”
Section: Concomitant Injuriesmentioning
confidence: 99%
“…However, only 1 of the 8 study designs used an immobilization period of 6 weeks. 18 Six of the study designs used a 2-to 4-week immobilization period, and the remaining study allowed some patients to discontinue immobilization at 1 week. One study protocol restricted combined movements of abduction with ER, whereas another restricted all passive ROM by a physical therapist or athletic trainer.…”
Section: Discussionmentioning
confidence: 99%
“…9,12,[15][16][17][18][19][20] In addition to the different types and degrees of instability among the studies, surgical technique varied from a painting style that left no remaining tissue between the treated areas to a striping technique that left minimal tissue between passes. Postoperative management also varied in the period of immobilization and progression of exercises.…”
Section: Capsular-plication Studiesmentioning
confidence: 99%
See 2 more Smart Citations